Product Innovation in Fruit Salads to Face Culinary Business Competition in Jember Regency : A Case Study of Alvi Salad - Dwi Novitasari; Joko Widodo; Mukhamad Zulianto (Inflasi : Jurnal Ekonomi, Manajemen dan Perbankan, 2024)
This study aims to describe the innovation of the product carried out by Alvi Salad. This research is a type of descriptive research with a qualitative approach. Data collection methods used are interviews, observations, and documents. Data analysis methods are data reduction, data presentation, and ng. The results showed that product innovation at Alvi Salad applied types of product development, including modulation-based product innovation, size-based product innovation, packaging-based product innovation, design-based product innovation, and effort reduction-based product innovation. Product innovation carried out by Alvi Salad includes innovative product characteristics so that it can improve product quality and ensure its products are still liked by consumers so that the market competition.